Chronic Granulomatous Aspergillus Synovitis: A Case Report - Aylin Canbolat Ayhan; Korhan Ozkan; Cetin Timur; Birol Aktas; Ayşe Bahar Ceyran (Mediterranean Journal of Hematology and Infectious Diseases)
Aspergillus can cause invasive disease of various organs especially in patients with weakened immune systems. Aspergillus synovitis and arthritis are uncommon types of involvement due to this infection. Approches to fungal osteoarticular infections are based on only case reports. This paper presents a rare case of chronic granulomatous Aspergillus synovitis in an immunocompromised 5-year old girl who was treated for acute lymphoblastic leukemia.